The European Commission's New NAIRU: Does it Deliver? - Sebastian Gechert; Katja Rietzler; Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
The NAIRU is a key component of potential output and as such critically affects output gap estimates. In May 2014, the European Commission changed its specification of the NAIRU for several countries and lowered its NAIRU estimates in the case of Spain from 26.6% to 20.7% for 2015. To test the dependence of the new NAIRU on unemployment versus structural factors, we run counterfactual simulations applying one-standard deviation shocks to actual unemployment and to the structural variable real unit labor costs. We find that the NAIRU in its new specification is still largely determined by actual unemployment. This calls in question both the interpretation of potential output estimates as barriers to more vigorous inflation-stable economic activity and the accuracy of structural deficit figures.
urn:nbn:de:101:1-2015032510680
Keywords: E23; E24; E31; 330; NAIRU; Kalman filter; output gap; euro area; structural deficit